Trends in Dynamic Capabilities Analysis in Management Literature: A Bibliometric Review - Hirzi Al Akbar, Emir; Iskandar, Yusuf (IJBLE Scientific Publications Community Inc., 2024)
The paper provides a comprehensive bibliometric analysis of research concerning Dynamic Capabilities (DC) within management literature. Its primary objective is to elucidate the landscape, evolution, and impact of DC, shedding light on its significance in organizational strategy. The analysis underscores a substantial growth trajectory in both the number of publications and the extent of citations, underscoring the burgeoning importance of DC in strategic management discourse. Moreover, collaboration patterns among researchers emerge prominently, indicating a robust engagement within the scholarly community and facilitating the exchange of knowledge. Noteworthy authors such as Z. Yousaf and Y.S. Chen is identified as an influential figure who has significantly contributed to shaping the scholarly discourse surrounding DC. The paper deliberates on the implications of these findings for strategic management research and practice. By offering insights into the current state and trends within the field of DC, it provides valuable guidance for future research endeavours and strategic decision-making processes. This analysis serves as a pivotal contribution to the advancement of knowledge in strategic management and organizational theory. In conclusion, the paper offers a meticulous examination of the research landscape pertaining to DC, highlighting its evolution, impact, and collaborative dynamics within the scholarly community. By delineating implications for both research and practice, it enriches the understanding of DC's role in organizational strategy and fosters avenues for further exploration in strategic management research.